Sustainable Improvement Alternatives to Animal Health Service Delivery Constraints in the Daffiama-Bussie-Issa District of the Upper West Region of Ghana - Cyril Babale Kelle; Frederick Adzitey; Norliza Julmohammad; Nurul Huda (ResearchGate, 2023)
Livestock production plays a key role in the livelihoods of rural people, serving as a source of employment, income, food, and security against the uncertainties of crop production. Yet delivering quality, affordable, and sustainable animal health services remains a major constraint in developing countries, including Ghana. This study explores the sustainable improvement alternatives to animal health service delivery constraints in Daffiama-Bussie-Issa District, Ghana. A total of 150 livestock farmers were randomly selected from fifteen communities and interviewed using semi-structured questionnaires. Statistical Product and Service Solutions (SPSS/IBM) version 20.0 was used to compute all descriptive statistical variables. Chi square analysis was done to check for the effect of some variables on others at a significant level of 5%. The study showed that 42.7% of the respondents were between 46-60 years. However, age had no influence on veterinary service patronage (X=8.672, df=3, p=0.34). Sixty-four percent of the respondents had no educational background. Also, education did not influence veterinary service patronage (X=2.357, df=5, p=0.798). Majority (41.3%) of the respondents traveled over 16 km to access animal health service providers. All (100%) of the respondents who had access to veterinary drugs practiced self-medication. The study revealed government animal health service providers as a sustainable animal health delivery channel. Based on these findings, livestock farmers should be encouraged to consult veterinary service providers before administering drugs and vaccines to their livestock. Keywords— Animal health; constraints; Daffiama-Bussi